Association of Differential Metabolites With Small Intestinal Microflora and Maternal Outcomes in Subclinical Hypothyroidism During Pregnancy - Li, Jingjing; Xu, Yajuan; Cai, Yanjun; Zhang, Miao; Sun, Zongzong; Ban, Yanjie; Zhai, Shanshan; Hao, Yingqi; Ouyang, Qian; Wu, Bo; Wang, Mengqi; Wang, Wentao (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To investigate the association of differential metabolites with small intestinal microflora and maternal outcomes in subclinical hypothyroidism (SCH) during pregnancy. Methods The plasma of pregnant women in the SCH group and control group was analyzed by liquid chromatography-mass spectrometry (LC-MS), obtaining differential metabolites. Then, methane and hydrogen breath tests were performed in both groups, and basic clinical data and maternal outcome information were collected. Finally, differential metabolites were analyzed for small intestinal bacterial overgrowth (SIBO) and pregnancy outcomes using Spearman correlation analysis. Results (1) Multivariate statistics: There were 564 different metabolites in positive ion mode and 226 different metabolites in negative ion mode. (2) The positive rate of the methane hydrogen breath test in the SCH group was higher than that in the control group (p<0.05). (3) KEGG pathway analysis revealed that differential metabolites were mainly involved in bile secretion, cholesterol metabolism, and other pathways. (4) Serum cholesterol (TC) and triglyceride (TG) levels and hypertensive disorder complicating pregnancy (HDCP) were higher in the SCH group (p<0.05), and newborn birth weight (BW) was lower than that in the control group (p<0.05). (5) SIBO was negatively correlated with glycocholic acid and BW, and positively correlated with TC. Glycocholic acid was negatively correlated with TG but positively correlated with BW. TG was positively correlated with HDCP. Conclusion Differential metabolites in the SCH group during pregnancy were disordered with small intestinal bacteria, which may affect pregnancy outcomes, and bile acids and cholesterol may be potential biomarkers for studying their mechanism of action.